Development of a receptive and expressive language handbook for hard-of-hearing disabilities in TKLB-B - Budiati, Eryana Fatimasari Retno; Nursalim, Mochamad; Mardliyah, Sjafiatul; Sartinah, Endang Pudjiastuti; Oktafiolita, Anggraini (Edelweiss Applied Science and Technology, 2025)
In kindergarten, one crucial area of development that requires emphasis is language development. This aspect holds immense significance for children as it enables them to articulate their thoughts, express desires, convey feelings, provide information, and communicate opinions and ideas, both verbally and non-verbally. However, not all children navigate language development tasks seamlessly in their early years, particularly those with hearing disabilities who attend kindergarten. Consequently, various obstacles may arise. In light of these challenges, it is essential for teachers to be equipped with appropriate guidance to effectively teach language skills to deaf children with disabilities, encompassing both receptive (listening) and expressive (speaking) aspects. This research endeavor aims to address these needs by producing a comprehensive handbook. The primary objective of this research is to create receptive (listening) and expressive (speaking) language handbooks tailored for individuals with hard-of-hearing disabilities in TKLB-B. Employing Thiagarajan's 4-D development model, this study adopts a developmental research approach, with modifications made specifically to the development stage. The study involved one material expert, one design expert, and one expert practitioner as subjects. Data collection techniques included validation questionnaires administered to material experts, media experts, and expert practitioners. Quantitative data analysis was conducted based on assessments provided by expert validators to determine the feasibility of the handbook, focusing on the scores obtained from the expert validation instruments. The expert validation test results indicate a percentage score of 86% (considered very good) from material experts, 87.5% (also very good) from design experts, and 76% (deemed good) from expert practitioners. These results affirm the suitability of the receptive (listening) and expressive (speaking) language handbooks for hard-of-hearing disabilities in TKLB-B, highlighting their efficacy for teachers facilitating language learning among kindergarten children with hearing impairments.